Inhibiting Factors in the Implementation of SIMGOS at RSUD Dr. Adnaan WD Payakumbuh, 2025 - Wulan Triani; Silvia Adi Putri; Rantih Fadhilya Adri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, Universitas Muhammadiyah Muara Bungo, 2025)
Introduction: Open Source Generic Management Information System (SIMGOS) Is an activity to provide knowledge to health service officers This system is a manifestation of the Ministry of Health in an effort to implement health activities and more sophisticated hospital information management by conducting research on the development of a more advanced and more advanced hospital management information system and has competitiveness in RSUD dr. Adnaan WD Payakumbuh HR capabilities in operating the SIMGOS application, as well as the lack of training received by staff so that the distribution of strategies has not been evenly distributed to all staff at the level of each unit. many staff do not understand and fully understand the strategic objectives of SIMGOS and how their role in supporting the implementation. and the lack of high implementation costs so that the availability of Hardware and Software is inadequate as well as the cost of training and maintenance is quite large so that it hinders the adoption of information technology that improves the quality of service. objective: to find out the description of the Inhibiting Factors for the Implementation of Open Source Generic Information System (SIMGOS) in RSUD dr. Adnaan WD Payakumbuh. This study uses a descriptive qualitative research. method: conducted at RSUD dr. Adnaan WD Payakumbuh. Conducted by Interview and Documentation Research. Results: The results of the research obtained from the HR Factor are that money users have difficulty in communicating with SIMGOS, especially Dpjp and senior nurses who have entered retirement age because they are accustomed to using manual recording so they feel the system slows down their work. Funding/budget factors are a very big obstacle without sufficient budget staff will find it difficult to carry out work because of budget limitations that make facilities and infrastructure inadequate, Strategy and method factors, especially in communication strategies, disrupt the implementation process due to limited SIMGOS system support devices. In addition, there is also a lack of understanding of staff in analyzing SIMGOS needs in the future, for example by completing the facilities and infrastructure used to conduct training for users and also increasing IT capabilities by carrying out training activities. Conclusion and Suggestion : For the Human Resources Factor: Overall, in improving human resources capabilities through training activities provided to staff to learn more about the SIMGOS Application, especially for senior doctors and nurses who are technologically illiterate in the outpatient room, to familiarize themselves with the SIMGOS application. In order to improve the quality of services in the hospital by requiring each user to go through a training stage to assess the extent of user understanding and performance in mastering the SIMGOS application, Funding/Budget Factor: Overall, Dr. Adnaan WD Payakumbuh Hospital faces funding/budget constraints, namely infrastructure such as many system needs that are not yet met due to a lack of funds and budget, resulting in inadequate system requirements. Strategy and Method Factor: The strategy and method have been structured and have been provided to each user, and after being provided, some users still do not read and apply the SOP provided by the hospital. Therefore, the hospital should be more assertive in implementing the Strategy and Method in using SIMGOS. Keywords: Overview of Inhibiting Factors in the Implementation of the Open Source Generic Management Information System (SIMGOS)